Perfil de mortalidade de idosos no Rio Grande do Norte: estudo comparativo entre duas faixas etárias e fatores relacionados - Oliveira, Tamires Carneiro de (2014)
Measures of mortality represent one of the most important indicators of health conditions. For comprising the larger rate of deaths, the study of mortality in the elderly population is regarded as essential to understand the health situation. In this sense, the present study aims to analyze the mortality profile of the population from 60 to 69 (young elders) and older than 80 years old (oldest old) in the Rio Grande do Norte state (Brazil) in the period 2001 to 2011, and to identify the association with contextual factors and variables about the quality of the Mortality Information System (SIM). For this purpose, Mortality Proportional (MP) was calculated for the state and Specific Mortality Rate by Age (CMId) , according to chapters of ICD- 10, to the municipalities of Rio Grande do Norte , through data from the Mortality Information System (SIM) and the Brazilian Institute of Geography and Statistics (IGBE). In order to identify groups of municipalities with similar mortality profiles, Nonhierarchical Clustering K-means method was applied and the Factor Analysis by the Principal Components Analysis was resort to reduce contextual variables. The spatial distribution of these groups and the factors were visualized using the Spatial Analysis Areas technique. During the period investigated, 21,813 younger elders deaths were recorded , with a predominance of deaths from circulatory diseases (32.75%) and neoplasms (22.9 %) . Among the oldest old, 50,637 deaths were observed, which 35.26% occurred because of cardiovascular diseases and 17.27% of ill-defined causes. Clustering Analysis produced three clusters to the two age groups and Factor Analysis reduced the contextual variables into three factors, also the sum of the factor scores was considered. Among the younger elders, the groups are called misinformation profile, development profile and development paradox, which showed a statistically significant association with education and poverty and extreme poverty factors, factorial sum and the variable related to underreporting of deaths. Misinformation profile remained in the oldest old group, accompanied by the epidemiological transition profile and the epidemiological paradox, that were statistically associated with the development and health factor, as well as with the variables that indicate the SIM quality: proportion of blank fields about the schooling and underreporting. It proposed that the mortality profiles of the younger elders and oldest old differ on the importance of the basic causes and that are influenced by different contextual aspects , observing that 60 to 69 years group is more affected by such aspects. Health inequalities can be reduced by measures aimed to improve levels of education and poverty, especially in younger elders, and by optimizing the use of health services, which is more associated to the oldest old health situation. Furthermore, it is important to improve the quality of information for the two age groups